Assessment of human capital development and its impact on the economy of the country - Baktymbet, S.S.; Baktymbet, A.S.; Serikkyzy, А. (BUKETOV BUSINESS REVIEW, 2021)
Object: In the article, the authors consider human capital as the driving force of the economy, identification of trends in relations, dynamics, prospects and results, where human capital influences the economic development of Kazakhstan. The aim of the study is to assess the critique of human capital development. Methods: The results of the research are based on the fundamental theoretical and empirical work of leading Kazakh and foreign scientists devoted to the analysis of the processes of accumulation and use of human capital. General scientific principles and methods were applied: analysis and synthesis, system approach. Findings: The basic components of basic human capital, such as education and training, Gross domestic product (GDP) growth, have been analysed. The authors analysed data from the UNESCO Institute for Statistics, Gross Enrolment Ratio (GER), which is an index illustrating the number of students enrolled at a given level of education. The results of the study showed that that health is the main component of human capital formation. T. Schultz suggested that health is a vital part of human capital formation, as it reflects living conditions. Life expectancy is the best indicator for determining health status. Conclusions: The need for investment in research and development was noted since any investment in science and technology increases human capital in the country. Therefore, the next indicator to be considered is an investment in research and development in Kazakhstan. An analysis was made of the main criteria for the development of human capital in Kazakhstan, which revealed the strengths and weaknesses of the current situation in the country. An assessment of the different levels of education shows that the gross enrolment ratio in primary and secondary schools is quite high. However, the GER for higher education is quite low compared to other developed countries.